Evaluation of three obturation techniques in the apical third of mandibular first molar mesial root canals using micro-computed tomography - Soram Oh; Hiran Perinpanayagam; Daniel J.W. Kum; Sang-Min Lim; Yeon-Jee Yoo; Seok Woo Chang; Woocheol Lee; Seung-Ho Baek; Qiang Zhu; Kee Yeon Kum (Elsevier, 2016)
Background/purpose: Recent studies have demonstrated a high incidence of isthmuses in mandibular first molar mesial roots, and intratubular mineralization following mineral trioxide aggregate obturation. This study assessed the filling quality of three obturation techniques in the apical 5 mm of mandibular first molar mesial root canals. Materials and methods: Sixty extracted human mandibular first molar mesial roots with two separate canals that had interconnecting isthmuses, were prepared to an apical size of 40/0.06. They were allocated to three groups of 20 roots for obturation by either cold lateral compaction (CLC) or the continuous wave of condensation (CW) that used gutta-percha and AH Plus sealer, or by an orthograde canal obturation using OrthoMTA. The obturated roots were scanned by micro-computed tomography and assessed for the volumetric ratio (%) of gutta-percha, sealer, and OrthoMTA within the main canals or isthmuses in the apical 5 mm area. Measurements were analyzed statistically for differences among three obturation techniques. Results: In the main canals, filled volume ratios were not significantly different among groups. Within isthmuses, the filled volume ratio for CLC was lower than in CW (P = 0.025) or OrthoMTA (P = 0.002). In isthmuses, the gutta-percha volume ratio in CLC was lower than in CW (P = 0.005), although the sealer volume ratio was higher than in CW (P = 0.049). Conclusion: CLC demonstrated lower filling densities in isthmuses in the apical region than either CW or OrthoMTA. Orthograde MTA obturation showed comparable filling quality to gutta-percha with sealer.